The Muslim Contribution to the Formation of United States Identity from the 19th to the 20st Century - Johan Septian Putra; Alkhairi Alkhairi (Journal of Philology and Historical Review, 2026)
This study examines the contributions of early Muslim communities—encompassing enslaved African Muslims and Middle Eastern immigrants from the late 19th to the early 20th century—to the process of shaping the United States as a pluralistic and multicultural nation. Although the presence of Muslims has been recorded since the period of slavery, mainstream American historical narratives have tended to marginalize the significant roles of the Muslim community in the nation’s social, cultural, and spiritual dynamics. Through a historical-qualitative approach and a "history from below" historiographical analysis, this research highlights how Muslims acted as active agents in confronting marginalization, preserving their religious and cultural identities, and building social structures that supported their community's sustainability. This study demonstrates that their contributions were not limited to religious aspects but also extended to economic, cultural, and civil rights struggles, particularly through African-American Islamic movements. These findings challenge the assumption that Islam is a foreign element in American history, instead asserting that it is an integral part of the nation's formation. By tracing the hidden vestiges of Muslim communities, this article aims to enrich a more inclusive and representative American historical narrative while contributing theoretically to the study of multiculturalism, national identity, and religious history in the United States.